Solute-Induced Retardation of Water Dynamics Probed Directly by Terahertz Spectroscopy - Heugen, U.; Schwaab, G.; Bründermann, E.; Heyden, M.; Yu, X.; Leitner, D. M.; Havenith, M. (Proceedings of the National Academy of Sciences - PNAS, 2006)
The dynamics of water surrounding a solute is of fundamental importance in chemistry and biology. The properties of water molecules near the surface of a bio-molecule have been the subject of numerous, sometimes controversial experimental and theoretical studies, with some suggesting the existence of rather rigid water structures around carbohydrates and proteins [Pal, S. K., Peon, J., Bagchi, B. & Zewail A. H. (2002) J. Phys. Chem. B 106, 12376-12395]. Hydrogen bond rearrangement in water occurs on the picosecond time scale, so relevant experiments must access these times. Here, we show that terahertz spectroscopy can directly investigate hydration layers. By a precise measurement of absorption coefficients between 2.3 THz and 2.9 THz we could determine the size and the characteristics of the hydration shell. The hydration layer around a carbohydrate (lactose) is determined to extend to 5.13 ± 0.24 Å from the surface corresponding to ≈123 water molecules beyond the first solvation shell. Accompanying molecular modeling calculations support this result and provide a microscopic visualization. Terahertz spectroscopy is shown to probe the collective modes in the water network. The observed increase of the terahertz absorption of the water in the hydration layer is explained in terms of coherent oscillations of the hydration water and solute. Simulations also reveal a slowing down of the hydrogen bond rearrangement dynamics for water molecules near lactose, which occur on the picosecond time scale. The present study demonstrates that terahertz spectroscopy is a sensitive tool to detect solute-induced changes in the water network.